A clinicopathological study of gestational trophoblastic disease in a tertiary care centre of southern Assam - Thakuria, Sailendra K.; Deka, Monoj K.; Sheikh, Shah A. (International Journal of Research in Medical Sciences, 2021)
Background: Gestational trophoblastic disease (GTD) covers a wide spectrum of benign and malignant conditions that arise from pregnancies with abnormal trophoblastic tissue development. It is a source of significant morbidity as well as increased risk of mortality from their complications if not identified and treated early enough. Our study aimed at the various clinicopathological features of GTDs along with their prevalence in a tertiary care centre. Methods: It was a retrospective cross-sectional study conducted over a period of 3 years from January 2017 to December 2019. All GTD cases were retrieved from department registries and analysed. Results: Out of 60 diagnosed cases of GTDs, 57 cases (95%) were Hydatiform mole. Invasive mole and choriocarcinoma were 2 cases (3%) and 1 cases (2%) respectively. Age ranged from 18-37 years. The most commonly affected age group was 20-25 years with 33 cases (55%). Most cases were presented in the first trimester presenting with bleeding per vagina. The majority of GTD cases belonged to blood group A and 50,000-<1,00,000 mlU/mL beta HCG level. Conclusions: Histopathological examination is helpful for confirmation of diagnosis.It is very important to follow up of such patients for early diagnosis of malignant trophoblastic tumors.